Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/cbm.2102
|View full text |Cite
|
Sign up to set email alerts
|

Dialectical behaviour therapy (DBT) for forensic psychiatric patients: An Italian pilot study

Abstract: Background Several previous randomised controlled trials of dialectical behaviour therapy (DBT) since Linehan's original have shown that it has an advantage over standard care or other psychological treatments, but focus is usually on suicide‐related behaviours, and little is known about its effect with offender‐patients. Aims To evaluate DBT with a group of offender‐patients in the Italian high intensity therapeutic facilities—the Residenze per l'Esecuzione delle Misure di Sicurezza (REMS), established under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…Hence the lack of significant improvement on the GAFS-8 in our study might be explained by the fact that alexithymia was not the main target of our intervention (Cameron et al, 2014 ). Alexithymia has rarely been measured in DBT protocols (Bianchini et al, 2019 ; Holmqvist Larsson et al, 2020 ), and it is still unknown whether and how it changes in other clinical populations during the course of DBT.…”
Section: Discussionmentioning
confidence: 99%
“…Hence the lack of significant improvement on the GAFS-8 in our study might be explained by the fact that alexithymia was not the main target of our intervention (Cameron et al, 2014 ). Alexithymia has rarely been measured in DBT protocols (Bianchini et al, 2019 ; Holmqvist Larsson et al, 2020 ), and it is still unknown whether and how it changes in other clinical populations during the course of DBT.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an evidence-based approach is strategic since this can allow the most reliable and effective assessment and treatment procedures to be adopted, particularly during emergency situations like the present one. Despite some preliminary effectiveness studies have been conducted in the Italian context (e.g., Bianchini et al 2019), more research and clinical work should be done to evaluate and adapt the psycho-rehabilitative programs to our context, since the attention given by forensic psychiatry professionals to evidence-based literature is still limited. The lack of evidence-based programs makes the REMS high-risk settings during the COVID-19 pandemic, as the spread of controversial information on the pandemic might have a strong impact on the inpatients' distress and increase the risk for violent acts (Campbell 2020).…”
Section: The Impact Of the Covid-19 Pandemic In Italymentioning
confidence: 99%
“…It also intervenes in low quality of life situations, reduces drug-seeking behavior, and helps patients function adaptively by accepting unpleasant emotions such as craving. 9,10,14 Research literature shows the efficacy and effectiveness of DBT in various comorbid problems and diseases such as suicide, 16 forensic psychiatric patients, 17 and irritable bowel syndrome. 18 Nevertheless, studies have reported contradictory results for the effectiveness of implementing DBT in various SUD populations.…”
Section: Introductionmentioning
confidence: 99%